Monitoring Astrocytic Ca2+ Activity in Freely Behaving Mice - Qin, Han; He, Wenjing; Yang, Chuanyan; Li, Jin; Jian, Tingliang; Liang, Shanshan; Chen, Tunan; Feng, Hua; Chen, Xiaowei; Liao, Xiang; Zhang, Kuan (Frontiers in Cellular Neuroscience, 2020)
Monitoring astrocytic Ca2+ activity is essential to understand the physiological and pathological roles of astrocytes in the brain. However, previous commonly used methods for studying astrocytic Ca2+ activities can be applied in only anaesthetized or head-fixed animals, which significantly affects in vivo astrocytic Ca2+ dynamics. In the current study, we combined optic fibre recordings with genetically encoded Ca2+ indicators (GECIs) to monitor astrocytic activity in freely behaving mice. This approach enabled selective and reliable measurement of astrocytic Ca2+ activity, which was verified by the astrocyte-specific labelling of GECIs and few movement artefacts. Additionally, astrocytic Ca2+ activities induced by locomotion or footshock were stably recorded in the cortices and hippocampi of freely behaving mice. Furthermore, this method allowed for the longitudinal study of astrocytic activities over several weeks. This work provides a powerful approach to record astrocytic activity selectively, stably and chronically in freely behaving mice.